Revitalizing Water Health: Unraveling Coliform Dynamics in Banjar Regency's River Ecosystem - Zubaidah, Tien; Hamzani, Sulaiman; Arifin, Arifin (Journal of Health Science and Prevention, 2024)
This study examined total coliform levels in rivers in Banjar Regency, South Kalimantan, and their effects on water quality and public health. Water samples were taken at eight river observation points using purposive sampling in a field survey. Analysis compared total coliform results to health criteria. To determine the link between total coliform and DO, correlation tests were performed. The overall coliform concentration exceeded the class I quality limit of 50 CFU/100 mL with 5050 to 52833,335 CFU/100 mL. Total coliform levels correlated -0.878 with DO levels, demonstrating contamination's ecological effects. High total coliform levels make river water unfit for sanitation and hygiene. Banjar Regency waterways must be cleaned to reduce bacterial contamination, protect public health, and allow safe water use. Addressing these issues will improve local prosperity and water sustainability